Modernisation of Memorising the Qur'an: A Comparison of Traditional and Modern Methods - Neliwati, Neliwati; Batubara, Rubiyah; Darwis, Muhammad; Desriadi, Desriadi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The purpose of this study is to analyse how the modernisation of Al-Qur'an memorisation methods affects both the comparison of traditional and modern methods on students' learning motivation, memorisation effectiveness, and long-term memory resilience at MTs Swasta Jabal Lubuk Raya. This research method is descriptive qualitative, or often known as postpositivistic, artistic, and interpretative research. Data collection instruments were observation, in-depth interviews, and document review. Data analysis using the flow of activities as proposed by Miles and Huberman, namely data reduction, data display and conclusions, drawing, and verification. The technique of sharpening the validity of data in this study is to use triangulation techniques. The results of this study are the modernisation of memorising the Qur'an with modern methods is significant to student learning motivation, especially in Gamification of learning to increase engagement and ease of access to increase the spirit of learning and improve the speed of memorisation to be higher and the existence of variations in memorisation methods according to student learning styles. While memorising the Qur'an with traditional methods has a significant effect on the effectiveness of student memorisation, especially in the quality of tajweed that is more guaranteed, and the memorisation process is more methodical, as well as a deeper understanding of the context of the verse. So it can be concluded that traditional Qur'anic memorisation methods and modern methods each have advantages and limitations. Therefore, the integration of both methods, i.e., combining the strengths of traditional methods and the convenience of modern technology, can produce more optimal results. This combination allows students to get direct correction from the teacher while utilising the convenience of self-learning with technology, thus increasing memorisation effectiveness and long-term memory retention. It also provides time flexibility for students without compromising the quality of teaching and learning.